Environmental Health Risk Analysis of Dust Exposure on Employees in PT. Cassia Co-op Indonesia in Jambi - Guspianto Guspianto; Intan Tri Thursina; Fitria Eka Putri (Faculty of Public Health, Hasanuddin University, Makassar, 2021)
The dust has a negative impact that can affect workers’ health. This study aimed to analyze the environmental health risks of dust exposure on workers at PT. Cassia Co-op Indonesia in Jambi. Descriptive quantitative research was conducted using an Analisis Risiko Kesehatan Lingkungan (ARKL) approach, including analysis of hazard identification, dose-response, exposure assessment, and risk characteristics. 61 respondents from the production division were selected as samples with a disproportionate stratified random technique. Data was collected using a questionnaire and Total Suspended Particulate (TSP) concentration from company’s secondary data. The results of measuring dust levels at 2 (two) points obtained a concentration value that was still below the threshold, but 77% of respondents experienced health problems related to TSP dust. The real-time intake value of TSP exposure of workers was not at risk of health problems (RQ<1) at both measurement points, and the intake lifespan value of TSP exposure was at risk of health problems (RQ>1) for all workers in the 15th year at point 1. It is recommended for companies to conduct regular health checks on workers, provide PPE and apply the standard use of PPE, make rules that prohibit smoking while working, and increase the location and frequency of testing for TSP dust levels in the company.